The Prophet's Emotional Intelligence with Children: An Analysis Based on Bradberry and Greaves Theory and Its Implications for Character Education - Irfan Hanif; Muhid (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2026)
Emotional intelligence is a fundamental competence that plays an important role in the formation of individual character; however, the development of this aspect has not received sufficient attention in contemporary education systems. This study aims to examine the emotional intelligence of the Prophet Muhammad in his interactions with children as depicted in the hadiths, and to analyze its implications for early childhood character education. This study employs a qualitative method through library research with an interdisciplinary approach that integrates hadith studies and psychological perspectives, particularly the emotional intelligence theory of Bradberry and Greaves. Primary data consisting of hadiths from authoritative hadith collections were analyzed using content analysis based on four dimensions of emotional intelligence: self-awareness, self-management, social awareness, and relationship management. The findings reveal that the Prophet's interactions with children clearly reflect all four dimensions. His behaviors of kissing his grandchild, carrying a child during prayer, prolonging prostration for a grandchild's safety, comforting a grieving child, reprimanding with gentleness, and teaching etiquette communicatively are manifestations of high emotional intelligence. The Prophet's exemplary conduct implies that early childhood character education must be built upon a foundation of affection, empathy, self-control, and positive communication. This study contributes to integrating hadith scholarship with modern psychology as an alternative framework for developing character education based on the Prophet's exemplary conduct.